A Conceptual Framework for Examining Trust towards Zakat Institution - Ghazali, Mohamad Zulkurnai; Saad, Ram Al Jaffri; Wahab, Muhammad Syahir Abdul (International Journal of Economics and Financial Issues, 2016)
This paper aims to propose a research conceptual framework for examining trust towards zakat institution amongst Moslem business owners. An extensive literature review method was utilized to identify and analyze the relevant literatures in order to propose the framework. This paper identified four factors that influence the trust, namely, shared values, communication, non-opportunistic behaviour and perception on distribution. Theoretical and practical implications of the paper as well as suggestions for future research were also discussed. Keywords: Zakat, Trust, Business, Conceptual Framework JEL Classification: L00